Editor (Guest) - Kaliviotis, Efstathios (My University, 2026)
Biofluid dynamics is a wide topic that merges mechanical and biological engineering as well as several fields of science. It involves a range of issues such as external and internal flows, how birds fly and animals swim, and internal blood and urinary flows. The complexities of such flows in terms of geometry, multi-scale effects, fluid–structure interactions, and, in many cases, non-Newtonian fluid properties (such as in small blood veins) impose significant challenges when it comes to studying these flows and, furthermore, to the design of devices aimed at controlling such flows.